Rice plants have three homologs of glutathione synthetase genes, one of which, OsGS2, codes for hydroxymethyl‐glutathione synthetase. (18th February 2019) - Yamazaki, Shinichi; Ochiai, Kumiko; Matoh, Toru
Abstract: Glutathione is a ubiquitous thiol tripeptide in land plants, and glutathione‐like tripeptides can also be found in some plant species. Rice ( Oryza sativa ) plants synthesize hydroxymethyl‐glutathione, in which the terminal glycine residue of glutathione is replaced by a serine residue; however, the biosynthetic pathway of hydroxymethyl‐glutathione has not been identified. We isolated three rice glutathione synthetase homologs, designated OsGS1, OsGS2, and OsGS3, and found that knockdown of OsGS2 via RNA interference markedly decreased hydroxymethyl‐glutathione concentration in rice plants. The in vitro enzyme assay, using purified recombinant protein, demonstrated that OsGS2 catalyzed the synthesis of hydroxymethyl‐glutathione from γ‐glutamylcysteine (γEC) and L‐serine in an ATP‐dependent manner. OsGS2 could also utilize glycine as a cosubstrate with γEC, but the enzyme‐substrate affinity for L‐serine was tenfold higher than that for glycine. These results indicate that OsGS2 codes for hydroxymethyl‐glutathione synthetase.